Georgia : Seventh Review Under the Extended Fund Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Georgia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
Georgia's performance under the Extended Arrangement has been positive, but the country is now facing a pronounced economic slowdown. Domestic and external demand remain weak, and service sector activity remains sluggish. Staff projects the economy to shrink by 5.1 percent this year followed by a gradual recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet